Transforming of Moderate Character Education in Islamic Educational Institutions - Umar, Mardan; Ismail, Feiby; Rahmi, Sri; Arifin, Zainal (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
The study focuses on moderate character education in Islamic educational institutions, especially those based on Islamic organizations such as Nahdlatul Ulama, Muhammadiyah, and Syarikat Islam. The study aims to reveal the moderate values of Islamic education institutions and their implementation in educational activities. The research uses a qualitative multisite approach, with data collection techniques through field observations, interviews, and documentation. This study includes Islamic educational institutions based on religious organizations, namely Nahdlatul Ulama, Muhammadiyah, and Syarikat Islam. Research locations are 1) Education and Social Foundation, Khadijah High School, East Java, as an Islamic educational institution based in Nahdlatul Ulama; 2) Muhammadiyah Boarding School, Yogyakarta; and 3) Cokroaminoto School, Surakarta, Central Java. The researchers performed data analysis using modified analytic induction analysis. Data analysis follows the stages of condensation, data display, verification, and conclusion. The results of this study show that each educational institution has moderate character values: 1) tawasuth; 2) tawazun; and 3) ta'addul/I'tidal. These values are embodied in learning to form a moderate Muslim character and become the mercy to the whole world (rahmatan lil alamin).